Contributing Factors of Family Resilience In Moslem Population - Latifa, Rena; Nihayah, Zahrotun; Rokhim, Minatur; Nurhasan, Nurhasan; Murniasih, Farhanah; Rismawati, Rismawati (Graduate School of UIN Syarif Hidayatullah Jakarta, 2024)
Family resilience refers to a family's capability to positively cope with challenging circumstances and emerge feeling stronger, more equipped, and more self-assured than before. This study aims to examine factors contribute to family resilience within the Muslim community. As the largest Muslim population globally, Indonesian Muslims can serve as a representative sample to illustrate the concept of family resilience within the Muslim population. We hypothesized that religiosity, and family communication may contribute to the formation of family resilience. Participants are Moslems from several area in Indonesia (N=406). The data analyzed by Multiple Regression Analysis. Result shows that religiosity and family communication significantly contribute to family resilience (R Square = 43.3). Family communication contributes higher (28.9%) than religiosity (14.3%). Some future recommendations: (1) programs and policies that encourage families to engage in shared religious practices and improve communication skills can be instrumental in fostering a supportive environment that helps families navigate challenges; (2) subsequent studies can explore mediating factors, such as socioeconomic status or external stressors, that may influence this relationship; longitudinal studies could assess how these dynamics evolve over time, particularly in response to changing societal conditions.